2020
DOI: 10.1111/ssqu.12865
|View full text |Cite
|
Sign up to set email alerts
|

A Democratic Emergency After a Health Emergency? Exposure to COVID‐19, Perceived Economic Threat and Support for Anti‐Democratic Political Systems

Abstract: Objectives. The urgency of the COVID-19 pandemic has led governments to impose restrictions on individual freedom and required citizens to comply with these restrictions. In addition, lockdowns related to COVID-19 have led to a significant economic crisis. We aimed to study how the pandemic and related economic threats have impacted support for anti-democratic political systems. Method. We analyzed data from a quota panel of the Italian adult population (N = 1,195), surveyed once before and once during the pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Before COVID-19, the literature mainly focused on the existential threats stemming from natural disasters (e.g., Russo et al, 2020), climate disasters (e.g., Zapata, 2018), and economic crises (e.g., Chen, 2010), showing the role of compensatory sources of control played by religion (e.g., Sibley and Bulbulia, 2012), the government (e.g., Oneal, Lian, and Joyner, 1996), and, most importantly for this study, anti-democratic authorities (Mirisola et al, 2014). In line with this, more recent studies indicated that the COVID-19 pandemic has led to an increase in religiousness and church attendance (e.g., Molteni et al, 2021), trust in the government (e.g., Bol et al, 2021), and anti-democratic attitudes and preferences (e.g., Amat et al, 2020;Roccato et al, 2020). Amat et al (2020), using a mix of experimental and survey data, showed that in Spain the COVID-19 pandemic has fostered a widespread demand for strong leadership and even a willingness to tackle the crisis by giving up some individual freedom.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Before COVID-19, the literature mainly focused on the existential threats stemming from natural disasters (e.g., Russo et al, 2020), climate disasters (e.g., Zapata, 2018), and economic crises (e.g., Chen, 2010), showing the role of compensatory sources of control played by religion (e.g., Sibley and Bulbulia, 2012), the government (e.g., Oneal, Lian, and Joyner, 1996), and, most importantly for this study, anti-democratic authorities (Mirisola et al, 2014). In line with this, more recent studies indicated that the COVID-19 pandemic has led to an increase in religiousness and church attendance (e.g., Molteni et al, 2021), trust in the government (e.g., Bol et al, 2021), and anti-democratic attitudes and preferences (e.g., Amat et al, 2020;Roccato et al, 2020). Amat et al (2020), using a mix of experimental and survey data, showed that in Spain the COVID-19 pandemic has fostered a widespread demand for strong leadership and even a willingness to tackle the crisis by giving up some individual freedom.…”
supporting
confidence: 83%
“…Amat et al (2020), using a mix of experimental and survey data, showed that in Spain the COVID-19 pandemic has fostered a widespread demand for strong leadership and even a willingness to tackle the crisis by giving up some individual freedom. In a longitudinal study performed in Italy, Roccato et al (2020) showed that COVID-19 exposure and perceived economic threats were positively associated with support for anti-democratic political systems, independent of participants' prepandemic predisposition toward them. But how long does this effect persist?…”
mentioning
confidence: 98%
“…Based on r = 0.51, p < .001, we computed a mean index for these items, with higher scores indicating support for anti-democratic political systems (cf. Roccato et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, research on the so-called "rally-round-the-flag" effect (Mueller, 1970) highlighted that, in difficult situations such as terrorist attacks, wars, or pandemics, people set aside political differences and show surging support for the figures or institutions representing the nation under assault (Esaiasson et al, 2020). In line with this contention, several studies revealed increased institutional trust during the COVID-19 crisis in various countries, including Italy (Bol et al, 2020;Falcone et al, 2020;Roccato et al, 2020). In turn, higher level of trust in the government with regard to its ability to control COVID-19 was significantly associated with greater compliance with measures such as frequent hand-washing, avoidance of crowded spaces, and social isolation or quarantine (Han et al, 2021; see also Harring et al, 2021).…”
Section: The Role Of Trust In Institutions Responsible For Managing the Pandemicmentioning
confidence: 96%